Analyzing mathematics beliefs of pre-service teachers using confirmatory factor analysis - Adnan Mazlini, Puteh Marzita, Zakaria Effandi (N/A, 2011)
Analyzing mathematics beliefs of pre-service teachers using confirmatory factor analysis by Adnan Mazlini, Puteh Marzita, Zakaria Effandi,